Study of the influence of behavioral skills on the development of media education of future specialists - Алимбаева, Сауле; Сматова, Клара; Мажибаев, Асылжан (Pedagogy and Psychology, 2021)
In the article, the study of the influence of behavioral skills on the development of media education of future specialists is considered as an actual problem. It is proved that behavioral skills are a real manifestation of activity and communication. It is proved that future specialists, combining theory and practice in their practice, along with mastering professional skills, find what is necessary among a huge amount of information, analyze, formulate and use it in their practice in a new way. It is established that the concepts of "Media Education", "Media literacy", "Psychological health" and "Psychological immunity" are interrelated. It is analyzed that the media is not only a carrier of information, but also provides the process of information perception. Using a special technique, it is shown that Coping is a type of behavior that reflects a willingness to solve life problems and is aimed at adapting to a specific situation. The methodology made it possible to identify priority coping strategies.